Foot-and-mouth disease vaccination induces cross-reactive IFN-γ responses in cattle that are dependent on the integrity of the140S particles - Bucafusco, Danilo (2014)
Interferon-γ (IFN-γ) recall responses against foot-and-mouth disease virus (FMDV) in FMD vaccinated cattle are utilized to study T-lymphocyte immunity against this virus. Here, a recall IFN-γ assay based on a commercial ELISA was set up using 308 samples from naïve and vaccinated cattle. The assay was used to study cross-reactive responses between different FMDV vaccine strains. Blood samples from cattle immunized with monovalent vaccines containing A24/Cruzeiro/Brazil/55, A/Argentina/2001 or O1/Campos/Brazil/58 strains were tested using purified-inactivated FMDV from homologous and heterologous strains. A24/Cruzeiro was the most efficient IFN-γ inducer in all vaccinated animals, both when included in the vaccine or as stimulating antigen. We demonstrate that this was mainly due to the structural stability of the whole viral particle. These results show that IFN-γ production relies on the presence of 140S particles that can maintain their integrity along the incubation process in vitro, and throughout the vaccine´s shelf-life, when used in vivo.